ANALISIS KESALAHAN BUKU MATEMATIKA MATERI PERSAMAAN GARIS LURUS KELAS VIII SMP SERTA ALTERNATIF PENYELESAIANNYA - Abdur Rohim; Nur Hidayati Laili; Genduk Rohmawati (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2021)
The purpose of this study is to analyze book errors in the material of Linear Equations and provide alternative solutions. The results of this study can be used as consideration in improving the book. This type of research is descriptive analytical research that describes a problem and the results are analyzed to find conclusions. The results showed that there were still some errors in the Junior High School Mathematics book for Linear Equations. These errors are spelling and writing errors, computational errors, problem errors and conceptual errors. The error is then given an alternative solution for further book development.